2023
DOI: 10.1108/bfj-05-2023-0357
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating emotions in the theory of planned behaviour: evidence of improved prediction in relation to sustainable food consumerism

Mara Martini,
Francesco La Barbera,
Susanna Schmidt
et al.

Abstract: PurposeThe theory of planned behaviour (TPB) and its extensions are often used to explain intentions to perform sustainable behaviours. Emotions can provide the impetus for action and should be considered in high-involvement situations, such as sustainable food purchase decisions. Therefore, the aim of this research work was to investigate whether the addition of different types of emotions (self-related, social and pro-active) to the TPB main constructs – attitude (ATT), subjective norm (SN) and perceived beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The theory of planned behavior is developed on the theory of reasoned action and states that intentions are shaped by consumers' attitudes and subjective norms (beliefs about others' attitudes) (Fishbein and Ajzen, 2009). According to TPB, behavioral intentions depend primarily on an individual's attitudes toward behavior and subjective norms, defined as the person's beliefs regarding the opinions of important others, such as family members and friends (Ajzen, 1991;Martini et al, 2023). Previously, it was shown that attitudes influence consumers' financial behavior (Sondari and Sudarsono, 2015;Cuccinelli et al, 2016) and cryptocurrency adoption (Cristofaro et al, 2022).…”
Section: Theoretical Background and Cryptocurrency Adoption Intention...mentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of planned behavior is developed on the theory of reasoned action and states that intentions are shaped by consumers' attitudes and subjective norms (beliefs about others' attitudes) (Fishbein and Ajzen, 2009). According to TPB, behavioral intentions depend primarily on an individual's attitudes toward behavior and subjective norms, defined as the person's beliefs regarding the opinions of important others, such as family members and friends (Ajzen, 1991;Martini et al, 2023). Previously, it was shown that attitudes influence consumers' financial behavior (Sondari and Sudarsono, 2015;Cuccinelli et al, 2016) and cryptocurrency adoption (Cristofaro et al, 2022).…”
Section: Theoretical Background and Cryptocurrency Adoption Intention...mentioning
confidence: 99%
“…Emotions play an essential role in consumer decision-making and can be considered while investigating behavioral intentions through the TPB; therefore, they can be included in the theoretical framework to predict behavioral intentions within TPB (Dur an et al, 2016;Martini et al, 2023). This study has focused on FOMO to extend TPB because emotions such as fear influence behavioral intentions (Kim et al, 2022a(Kim et al, , 2022b, and to the best of our knowledge, no previous study has examined CCAI within TPB by considering the impact of FOMO.…”
Section: Fear Of Missing Outmentioning
confidence: 99%